STRATEGI KOMUNIKASI PEMASARAN BARANG DAGANG DI MODERN MARKET (Studi Kasus Pada Toko Familymart): STRATEGI KOMUNIKASI PEMASARAN BARANG DAGANG DI MODERN MARKET (Studi Kasus Pada Toko Familymart) - Pratama Yuono, Dedik; Eriyanti, Helvi (KAGANGA KOMUNIKA: Journal of Communication Science, 2024)
In the era of globalization, companies in the same industry face increasingly intense competition. To stay ahead, companies need to develop effective marketing communication strategies. This is evident in the retail industry, where various retail formats are constantly evolving to meet the needs of modern consumers. This study examines the marketing communication techniques used by FamilyMart, a retail company in Indonesia. The study's findings show that FamilyMart leverages social media platforms to promote products and raise brand awareness. FamilyMart also integrates offline and online marketing strategies, identifies customer preferences, and measures the success of its strategies through sales data analysis and customer engagement metrics. In addition, in-store interactions and promotions also play a key role in raising product awareness. FamilyMart creates and maintains relationships with customers through effective communication and loyalty programs. The company also adjusts its strategies to reflect changing trends and consumer needs.  Keywords: Marketing Communication Strategies, Modern Market, Familymart